Halophytes: What are their Defines, Important, and their Strategies to be Live in Saline Habitats? (A Review) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
Halophytes or saline plants characterized in their ability to live and give production in saline soils or in other saline habitats. They refer to plants that can live in high salts habitats like saline marshes and saline deserts, and can give relatively a high production of biomass in such habitats. They are very important due to their different uses of them as food, fodder, drugs and many other different important. They may solve salinity problem tolerant or avoidant species by several adaptations which may by morphological, anatomical or cellular modifications. In this review tend to answer the main questions related to halophytes which including: what are their defines, important, and their strategies to be live and give good productivity  in saline habitats?